DUALITAS IMPLEMENTASI KEWENANGAN PUSAT DALAM PENATAAN DAERAH OTONOMI BARU: ANTARA POLITIK STRATEGIS DAN EFISIENSI TEKNOKRATIK - Shafa Suhaila; Mutiara Andini; Oriza Satifa Wahyuni; M. Daris Alfi Putra Nurhadi; Muhammad Sahriadi Lubis (JURNAL ILMIAH RESEARCH STUDENT, 2026)
This study aims to analyze the duality in the implementation of the central government’s authority in organizing new autonomous regions after the enactment of Law No. 23 of 2014. Using a literature study and comparative analysis approach, this research examines the policy contrast between the acceleration of provincial expansion in Papua and the prolonged postponement of expansion proposals in other regions. The results show that the central government applies a double standard in decision-making regarding regional expansion. In Papua, considerations of strategic politics, national security, and territorial integration dominate the policy process, sidelining technical-economic aspects. Meanwhile, expansion proposals outside Papua are strictly evaluated based on fiscal efficiency, administrative readiness, and local elite harmony. This duality reflects a policy shift from regional autonomy principles to an elastic centralistic instrument, where law is applied selectively according to national political interests. As a result, the meaning of autonomy is diluted, legal uncertainty arises in the regions, and new dependencies between regions and the central government are created. This study recommends the need for transparency, consistency, and an objective roadmap for regional arrangement so that expansion policy does not merely serve as a political tool, but genuinely supports governance effectiveness and interregional justice.